Early Intervention Services During the COVID-19 Pandemic in Spain: Toward a Model of Family-Centered Practices - Vilaseca, Rosa; Ferrer, Fina; Rivero, Magda; Bersabé, Rosa M. (Frontiers in Psychology, 2021)
Early intervention services (EIS) worked hard to continue serving children and their families during the COVID-19 lockdown, using online applications. This study aimed to determine families’ and professionals’ perceptions of the functioning of the early intervention (EI) model in Spain during the pandemic. The study sample comprised two subsamples: 81 families of children attended at an EIS (72 mothers and 9 fathers) and 213 professionals recruited from EIS. The survey was conducted online several weeks after the end of the strict lockdown in Spain. Descriptive statistics of the questionnaire answered by families and professionals were compiled, comparisons were made between the families’ and the professionals’ responses, and the relationships with several sociodemographic variables were analyzed. The results indicated that parents who cared for their children and were fully responsible for housework, parents who had used telematic tools before the lockdown, and younger professionals had a more positive perception of the EI model and the incorporation of family-centered practices (FCP) during the pandemic. The results also showed statistically significant differences in some items between parents and professionals: for example, professionals perceived more advantages than families during the lockdown, quoting the greater participation of families in the intervention and a greater focus on families’ needs. The data obtained from professionals suggested a more positive attitude toward FCP: however, the results show that they continued to adopt a directive role in the intervention, a position that is at odds with the tenets of FCP. There is a clear need for more training if a paradigm shift to FCP is to be achieved. Families’ and caregivers’ perceptions of telerehabilitation, and their adherence to telerehabilitation programs, are discussed. The implications of this study with regard to guiding future telematic interventions and family support are also considered.